2020
DOI: 10.5812/ans.91857
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Endurance Training and Royal Jelly Consumption on Motor Balance and Pain Threshold in Animal Model of the Alzheimer Disease

Abstract: Background:The Alzheimer disease (AD) induces the central and peripheral nervous system disruption by increasing oxidative stress; therefore, it induces disruption of the physical condition as well as occurrence of chronic pain. Objectives: The present study aimed at investigating the interactive effects of endurance training (ET) on positive and negative slope and royal jelly (RJ) consumption on motor balance and pain threshold in animal model of AD. Methods: The current experimental study was conducted on 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…There is limited information about the interactive effect of exercise and RJ and their antioxidant effect; however, exercise and RJ interactively increased serotonin gene expression levels (3), motor balance (12), and memory and learning (1) in rats with AD. Concerning the interactive effects, the present study showed that ST along with RJ had interactive effects on increasing GPx and decreasing SOD gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is limited information about the interactive effect of exercise and RJ and their antioxidant effect; however, exercise and RJ interactively increased serotonin gene expression levels (3), motor balance (12), and memory and learning (1) in rats with AD. Concerning the interactive effects, the present study showed that ST along with RJ had interactive effects on increasing GPx and decreasing SOD gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, to use RJ daily, 250 mg of RJ was immediately removed from the temperature of -21˚C with a scalpel and dissolved in 3 mL of normal saline. Immediately after ensuring their dissolution by shaker, the RJ groups were injected with 0.3 mL of RJ solution to each rat (12,13,18). Next, 48 hours after the last training session, the rats were anesthetized with 10% ketamine (50 mg/kg body weight) and 2% xylazine (10 mg/kg body weight) after about 5 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats with AD were then randomly assigned to six groups, including: The ETPS (+ 15) and ETNS (-15) groups trained for eight weeks, five 60-minute sessions per week at 16 m/min (10). The daily dose of royal jelly prepared by Marvdasht Agricultural Jihad and approved by the experts of this center was 100 mg/kg RJ as peritoneal injection (Hosseini et al n.d. ( 10)).…”
Section: Methodsmentioning
confidence: 99%
“…However, due to the contradictions in the role of high intensity exercise on oxidative stress and in ammation, it seems that the use of some natural antioxidants along with exercise activities has an enhancing role in treating diseases, or preventing injuries caused by training [23,24]. Among these, royal jelly (RJ), made by bee's submandibular glands, is used in the treatment of some diseases, including autoimmune diseases, due to its anti-in ammatory, antioxidant, anti-apoptotic properties as well as improving metabolism [25].…”
Section: Introductionmentioning
confidence: 99%